2009
DOI: 10.1021/ie8015329
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Inclusion Complexes of β-Cyclodextrin−BITC and β-Cyclodextrin−PEITC

Abstract: Benzyl isothiocyanate (BITC) and phenylethyl isothiocyanate (PEITC) are two poorly water-soluble plant components that can form inclusion complexes with β-cyclodextrin (β-CD), namely, β-cyclodextrin−BITC and β-cyclodextrin−PEITC, that are two water-soluble complexes. The inclusion complexes were prepared by two independent processes: physical mixing and coprecipitation. The content of guest molecules in the complexes was measured by UV spectrophotometry. Response surface design (RSD) was applied to optimize th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 19 publications
2
16
0
Order By: Relevance
“…Relatively low QR inducing activity of root samples despite of high glucosinolate and HP concentration could be explained by volatility of HPs in root samples. As mentioned previously, PEITC and erucin have very low water solubility, which has been previously reported [ 19 , 26 ]. Previous studies could not detect PEITC in hydrolyzed watercress extracts due to water solubility [ 31 ].…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…Relatively low QR inducing activity of root samples despite of high glucosinolate and HP concentration could be explained by volatility of HPs in root samples. As mentioned previously, PEITC and erucin have very low water solubility, which has been previously reported [ 19 , 26 ]. Previous studies could not detect PEITC in hydrolyzed watercress extracts due to water solubility [ 31 ].…”
Section: Resultssupporting
confidence: 62%
“…For both broccoli and collards, relatively small amounts of PEITC (1.32 and 1.56 μmol/g DW, , respectively) were detected in root tissues compared to its precursor, gluconasturtiin (16.9 and 20.8 μmol/g DW, respectively) in the same tissues. This discrepancy is probably due to its lower solubility in water compared to other compounds, which has been previously reported [ 19 , 26 ]. Although SF has a water solubility of 8.0 mg/mL, PEITC has only 0.051 mg/mL of water solubility [ 27 ].…”
Section: Resultsmentioning
confidence: 81%
“…The thermogram of the sonochemically formed complexes showed a peak shift at around 105 °C. The shift of peak to the lower temperature and intensification/deepening of the peak around 220 °C could be attributed to the change in the properties followed by complete complexation thus, confirming the interaction between BITC and CDs (30). The high thermal stability of the complexes was proved by the non-isothermal thermogravimetric analysis conducted in our previous work (29).…”
Section: Resultsmentioning
confidence: 54%
“…The inclusion complex kept antibacterial activity, and then the authors speculate that they also should keep the pharmacological properties. Yuan, Yao, Shen & Mao (2009) optimized the formation of benzyl- and phenyl isothiocyanates inclusion complexes using β-cyclodextrin, through response surface methodology. They concluded that temperature and mass ratio were the most significant factors that affect encapsulation.…”
Section: Microencapsulation Of Sulforaphane and Isothiocyanatesmentioning
confidence: 99%